The Influence of Cultural Patterns on Family Relations in Serbian Communities in Kosovo and Metohija - Petrović, Marina D. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The family, as the basic social unit, plays a central role in transmitting cultural patterns and value systems across generations. In Serbian communities in Kosovo and Metohija, this process is shaped by complex historical, political, and security circumstances that influence the stability and functioning of family relations. The paper examines the impact of traditional cultural patterns on the formation of marital, parental, and inheritance relations, with particular emphasis on the tension between customary law and contemporary legislation.The research adopts a multidisciplinary approach combining legal and sociological analysis. The legal perspective provides insight into the principles of Serbian family and inheritance law, while the sociological dimension examines how these norms are internalized and practiced within local communities. The study also incorporates comparative perspectives from other post-conflict societies in order to situate the Kosovo and Metohija context within a broader framework of social transformation.The findings indicate that patriarchal cultural models remain deeply embedded in social life and continue to shape gender roles, family authority, and inheritance practices. Despite formally established legal equality, traditional norms often prevail in everyday practice, particularly in inheritance relations, where women frequently renounce their legal rights in favor of male relatives. The persistence of such practices reveals a tension between law and tradition, highlighting the challenges faced by the legal system in promoting gender equality and social justice.The paper concludes that harmonizing customary and modern legal norms requires a gradual and culturally sensitive approach grounded in education, institutional support, and respect for local identity. Such an approach would enable the preservation of cultural heritage while ensuring the protection of fundamental human rights, which remains essential for the sustainable development of Serbian communities in Kosovo and Metohija
Keywords: cultural patterns; family relations; Kosovo and Metohija; customary law; social change; sociology of law